Policy Implementation Challenges and Barriers to Access Sexual and Reproductive Health Services Faced By People With Disabilities: An Intersectional Analysis of Policy Actors' Perspectives in Post-Conflict Northern Uganda - Muriel Mac-Seing; Emmanuel Ochola; Martin Ogwang; Kate Zinszer; Christina Zarowsky (Kerman University of Medical Sciences, 2022)
Background Emerging from a 20-year armed conflict, Uganda adopted several laws and policies to protect the rights of people with disabilities, including their sexual and reproductive health (SRH) rights. However, the SRH rights of people with disabilities continue to be infringed in Uganda. We explored policy actors' perceptions of existing prodisability legislation and policy implementation, their perceptions of potential barriers experienced by people with disabilities in accessing and using SRH services in post-conflict Northern Uganda, and their recommendations on how to redress these inequities. Methods  Through an intersectionality-informed approach, we conducted and thematically analysed 13 in-depth semi-structured interviews with macro level policy actors (national policy-makers and international and national organisations); seven focus groups (FGs) at meso level with 68 health service providers and representatives of disabled people's organisations (DPOs); and a two-day participatory workshop on disability-sensitive health service provision for 34 healthcare providers.  Results We identified four main themes: (1) legislation and policy implementation was fraught with numerous technical and financial challenges, coupled with lack of prioritisation of disability issues; (2) people with disabilities experienced multiple physical, attitudinal, communication, and structural barriers to access and use SRH services; (3) the conflict was perceived to have persisting impacts on the access to services; and (4) policy actors recommended concrete solutions to reduce health inequities faced by people with disabilities.  Conclusion  This study provides substantial evidence of the multilayered disadvantages people with disabilities face when using SRH services and the difficulty of implementing disability-focused policy in Uganda. Informed by an intersectionality approach, policy actors were able to identify concrete solutions and recommendations beyond the identification of problems. These recommendations can be acted upon in a practical road map to remove different types of barriers in the access to SRH services by people with disabilities, irrespective of their geographic location in Uganda.